Structural behavior of RC beams strengthened with prestressed near surface mounted technique using basalt FRP bars. (1st January 2022) - Sokairge, Hesham; Elgabbas, Fareed; Elshafie, Hany
Highlights: NSM and prestressed NSM are effective techniques that greatly enhanced the flexural behaviour of strengthened RC beams. BFRP bars showed superior performance in strengthening of RC beams using NSM and prestressed NSM techniques. The initial prestressing level greatly influence the flexural behavior of strengthened RC beams. The high creep rupture strength of BFRP bars offers it a priority for strengthening RC beams using prestressed NSM technique compared to GFRP bars. Abstract: This research aimed at studying the flexural behavior of RC beams strengthened with near surface mounted (NSM) technique using basalt FRP (BFRP) bars to assess their efficiency for strengthening RC beams in order to be introduced as an alternative to other types of FRP bars. Moreover, this study investigated a new type of strengthening technique, named prestressed near surface mounted (PNSM) technique, which is expected to offer lots of advantages owing to combining two well-known "external prestressing" and "NSM" techniques. The variables considered in this study were the strengthening effect (unstrengthened and strengthened), the type of the FRP bars (BFRP and GFRP), the strengthening technique (NSM and PSNM), the initial prestressing level (30% and 50% of ultimate tensile capacity of BFRP bars), and the position of NSM FRP bars (bottom and side). The test results demonstrated the efficiency of using BFRP bars for strengthening RC beams with NSM and PNSM techniques. Additionally, BFRP bars offered additional advantage compared to GFRP bars when strengthened with PNSM technique owing to its higher creep rupture strength. Moreover, the test results proved that strengthening of RC beams with PNSM technique offers superior enhancement in the pre-cracking stage compared to NSM technique while sacrificing a great portion of beam's ductility.